2018
DOI: 10.1038/s41419-018-1057-0
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 deficiency leads to induction of abnormal glycolysis in diabetic kidney with fibrosis

Abstract: The regulation of aberrant glucose metabolism in diabetes associated-kidney fibrosis is not well known. In this study we found the suppression of SIRT3 protein level in diabetic kidney, displays responsibility in fibrogenic programming associated with aberrant glycolysis and such abnormal glycolysis is the therapeutic target in diabetes associated-kidney fibrosis. When analyzing different strains of streptozotocin-induced diabetic mice model (fibrotic model: CD-1, less fibrotic model: C57Bl6), we found SIRT3 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
167
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(170 citation statements)
references
References 61 publications
2
167
1
Order By: Relevance
“…Streptozotocin (STZ) induced diabetic CD-1 mouse is a validated model of diabetic kidney disease [28,29]. It has been shown that DPP-4 protein is found higher in the kidneys of diabetic CD-1 mice as compared to kidneys of non-diabetic mice [11].…”
Section: Inhibition Of Ace Suppresses Dpp-4 and Associated Tgfβ Signamentioning
confidence: 99%
“…Streptozotocin (STZ) induced diabetic CD-1 mouse is a validated model of diabetic kidney disease [28,29]. It has been shown that DPP-4 protein is found higher in the kidneys of diabetic CD-1 mice as compared to kidneys of non-diabetic mice [11].…”
Section: Inhibition Of Ace Suppresses Dpp-4 and Associated Tgfβ Signamentioning
confidence: 99%
“…Sirtuin 3 (Sirt3) is a member of NAD + -dependent deacetylase; it is a key regulator of the mitochondrial respiratory chain and plays an important role in the pathophysiology of various diseases, such as diabetes and metabolic syndrome, and aging [23]. Existing studies have indicated that overexpression of Sirt3 is able to inhibit fibrosis in a variety of animal disease models [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the metabolism of renal epithelial cells (Rowe et al, 2013). TGFβ1 is a well‐known mesenchymal inducer (Grande et al, 2015), suppresses fatty acid oxidation (Kang et al, 2015) and induces glucose metabolism in high‐glucose‐treated cultured renal tubular epithelial cells (TECs) (Srivastava et al, 2018). Renal tubular epithelial cells require high levels of baseline energy consumption and are highly dependent on fatty acid oxidation (Kang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Kidney fibrosis is associated with an increased rate of sirtuin 3 (SIRT3) deficiency‐linked abnormal glucose metabolism and mesenchymal activation (Srivastava et al, 2018). SIRT3 is a major mitochondrial deacetylase that targets several diverse enzymes involved in central metabolism resulting in the activation of many oxidative pathways (Kim et al, 2010; Yin & Cadenas, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation